2011
DOI: 10.1038/jp.2010.213
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic detection of pulmonary hypertension in extremely low birth weight infants with bronchopulmonary dysplasia requiring prolonged positive pressure ventilation

Abstract: Objective: The goal of this study was to delineate the epidemiology of echocardiographically diagnosed pulmonary hypertension (PH) in extremely low birth weight (ELBW) infants with bronchopulmonary dysplasia (BPD) requiring prolonged positive pressure ventilation (PPV), and to determine the independent relationship between PH and mortality in these patients. Result:We identified 216 patients (19%) with BPD requiring prolonged PPV among 1156 ELBW infants. Of these patients, 41% received echocardiography after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
166
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 31 publications
3
166
1
Order By: Relevance
“…Forty-one percent of these infants were evaluated with echocardiography, with 37% having evidence of pulmonary hypertension. 10 Thirty-eight percent of the 29 infants with pulmonary hypertension died, as compared with 14% of the 49 infants without pulmonary hypertension. 10 Khemani et al 15 studied 42 infants with BPD and pulmonary hypertension at a median age of 4.8 months and noted that 38% of these infants died during follow-up.…”
Section: Figurementioning
confidence: 99%
“…Forty-one percent of these infants were evaluated with echocardiography, with 37% having evidence of pulmonary hypertension. 10 Thirty-eight percent of the 29 infants with pulmonary hypertension died, as compared with 14% of the 49 infants without pulmonary hypertension. 10 Khemani et al 15 studied 42 infants with BPD and pulmonary hypertension at a median age of 4.8 months and noted that 38% of these infants died during follow-up.…”
Section: Figurementioning
confidence: 99%
“…1,3,4 Mortality rates in infants with BPD-PH are 4-fold greater than in infants without PH, with the majority of deaths linked directly to PH. 3,5 Supplemental oxygen is the mainstay of therapy for patients with BPD-PH. [6][7][8] However, survival rates of infants with BPD-PH treated by using supplemental oxygen are 61% and 52% at 1 and 2 years of age, respectively.…”
mentioning
confidence: 99%
“…PAH is common in infants with BPD, with an estimated incidence of 18%-25% of preterm infants, [79][80][81] and is associated with high mortality (30%-40%), especially if sustained beyond the first months of life. [82][83][84][85] Although long-term studies of BPD have primarily focused on late abnormalities of airway function, PVD can also persist into childhood and adult life. 79,[86][87][88][89] Tepper and colleagues 88 have reported that infants with even mild BPD have decreased diffusion capacity when corrected for lung volume, in comparison with age-matched term controls, suggesting that BPD infants may have decreased alveolar surface area available for gas exchange.…”
Section: Pvd In Bpdmentioning
confidence: 99%